Mechanism underlying circRNA dysregulation in the TME of digestive system cancer - Wu, Zeyu; Yu, Xiao; Zhang, Shuijun; He, Yuting; Guo, Wenzhi (Frontiers in Immunology, 2022)
Circular RNAs (circRNAs) are a new series of noncoding RNAs (ncRNAs) that have been reported to be expressed in eukaryotic cells and have a variety of biological functions in the regulation of cancer pathogenesis and progression. The TME, as a microscopic ecological environment, consists of a variety of cells, including tumor cells, immune cells and other normal cells, ECM and a large number of signaling molecules. The crosstalk between circRNAs and the TME plays a complicated role in affecting the malignant behaviors of digestive system cancers. Herein, we summarize the mechanisms underlying aberrant circRNA expression in the TME of the digestive system cancers, including immune surveillance, angiogenesis, EMT, and ECM remodelling. The regulation of the TME by circRNA is expected to be a new therapeutic method.